Le microcosme insulaire de Jules Verne dans L’Île mystérieuse. De l’île de la Désolation à l’île Lincoln - Bertrand, Didier (Romanica Silesiana)
This article means to demonstrate that the complexity of Mysterious Island, stemming from the description of the place, this silent but omnipresent character, prevent it from being limited to the young readership intended by Hetzel, Verne’s editor. The anticolonial and antislavery discourse established as the ideological principle early on, is debunked by a counter‑discourse based on new knowledge of anthropology. Conclusions about Verne’s response to Defoe are also addressed. Key words: Daniel Defoe, Robinson Crusoe, robinsonnade, Jules Verne, L’Île mystérieuse, imperialism, colonialism, children’s literature, intertextuality